2020
DOI: 10.7150/thno.39502
|View full text |Cite
|
Sign up to set email alerts
|

A sericin/ graphene oxide composite scaffold as a biomimetic extracellular matrix for structural and functional repair of calvarial bone

Abstract: Bone defects affect millions of people worldwide each year, leading to severe disabilities. Biomimetic scaffolds mediated tissue regeneration represents a promising alternative for bone repair. However, the major problem associated with most currently clinical available artificial bone substitutes (scaffolds) is that they mainly possess filling function but lack of osteo-induction abilities. Therefore, development of biomaterials with osteo-induction property for effective bone regeneration is highly desired.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…Stem cells from different sources could be used as progenitor cells in the process of bone formation, so their recruitment and osteogenic differentiation were key factors for effective bone regeneration. GDs were proved to have the ability of osteogenic induction, [144][145][146][147][148][149][150][151][152] as shown in Table 4. In this subsection, the signaling pathways involved in GDs-induced bone regeneration were discussed, including which signaling pathways of osteogenic differentiation of stem cells from different sources were affected by GDs and the effect of GDsrelated parameters on the signaling pathway.…”
Section: Mechanism Of Gds-induced Bone Regeneration Possible Signalinmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells from different sources could be used as progenitor cells in the process of bone formation, so their recruitment and osteogenic differentiation were key factors for effective bone regeneration. GDs were proved to have the ability of osteogenic induction, [144][145][146][147][148][149][150][151][152] as shown in Table 4. In this subsection, the signaling pathways involved in GDs-induced bone regeneration were discussed, including which signaling pathways of osteogenic differentiation of stem cells from different sources were affected by GDs and the effect of GDsrelated parameters on the signaling pathway.…”
Section: Mechanism Of Gds-induced Bone Regeneration Possible Signalinmentioning
confidence: 99%
“…Firstly, when GDs were used alone and GDs were combined with other materials, the signaling pathways involved in GDs-induced bone regeneration were different, which might be due to the change of the surface charge and groups after GDs were introduced into the matrix. For example, Qi et al 144 prepared sericin methacryloyl/GO (SMH/GO) composite hydrogel as bone repair material by photo-crosslinking. The results of in vivo experiments showed that the hydrogel containing GO had a better bone regeneration effect, and the structure and function of rat skull defect model were repaired within 12 weeks.…”
Section: Mechanism Of Gds-induced Bone Regeneration Possible Signalinmentioning
confidence: 99%
“…In addition, carbon-based nanomaterials, such as GO and single-/multi-walled carbon nanotubes, offer great promise for cancer photothermal therapies because of their strong NIR light absorbance, excellent photothermal performance and satisfactory cytocompatibility 68 - 71 . It also has been reported that carbon-based nanomaterials can effectively improve bone regeneration by inducing the directional migration and osteogenic differentiation of BMSCs 72 , 73 . For example, GOā€‘modified biofunctional tricalcium silicate bone cement and TCP bone scaffolds have been fabricated for cancer therapy and bone tissue regeneration 59 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Sericin is a natural protein extracted from silkworm cocoons. Due to its good biocompatibility, biodegradability, low-immunogenicity and natural cell adhesion [ 28 , 29 ], sericin has been widely used to develop tissue engineering scaffolds or nanocarriers for drug delivery [ [30] , [31] , [32] , [33] , [34] , [35] ], as well as the silk fibroin [ 36 , 37 ]. Hence, we proposed to prepare a pulmonary delivery system composed of (1) sericin microparticles (SMPs) as the core carrier, that can effectively encapsulate anticancer drug, and (2) tannic acid (TA) and ferric irons (Fe 3+ ) based metal-organic networks (MON) coating on SMPs ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%